Increasing the wheat yield of Kansas - Gernert, Walter Byron (My University, 1907)
Introduction: The history of winter wheat in Kansas is one of the most interesting chapters in agricultural progress. Every Kansan refers with pride to the developement of the industry from the time farming was commenced a half century ago in the small river valleys of the eastern part of the state, when the state was considered to be more or less a desert, to the present time when Kansas has become one of the greatest wheat producing sections of the world. At the time when wheat was first grown in this State, very little was known about the hard winter wheat for which Kansas has since become famous. Soft wheats were the only varieties grown and when the hard wheats were first introduced it was not thought that they would prove successful. It has scarce been forty years since the introduction of hard winter wheat by the Mennonite immigrants from the Russian Crimea. These hardy newcomers with remarkable foresight settled in the central part of the state and sowed small quantities of the seed-wheat which they had brought with them. This central group of counties has since developed into the principal wheat producing section of the state, and Kansas has come to occupy the foremost rank in the production of hard winter wheat. Kansas raises more wheat than any other state in the Union, yet we must confess that this is due to the number of acres sown rather than to the large yield per acre. The average yield of wheat per acre in Kansas is nearly one-third bushels less than the average for all the states, many of which are less adapted to wheat growing than our own state. The average yield for the state for the last ten years has been 13.1 bushels per acre. Under more favorable cropping conditions, many of which...
Citation: Gernert, Walter Byron. Increasing the wheat yield of Kansas. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Wheat; Wheat Growing; Kansas Agriculture; Theses